Apoptose e maturação placentária bovina: um estudo imunoistoquímico e morfométrico - Tatiane Furtado de Carvalho (2014)
Placental release after birth involves loss of maternal-fetal adhesion and occurs only after complete maturation of the placentome, which is related to the decrease in cellularity of fetal and maternal tissues. Apoptosis is required for both the normal maturation and release of the placenta after birth. The aim of this study was to evaluate the occurrence of apoptosis in samples of placenta of cows in different stages of gestation. Samples of 15 healthy cows placentomes 4 (n = 5), 6 (n = 5) and 9 (n = 5) months of gestation were harvested and processed for routine histology, immunohistochemistry and histochemistry. The slides were stained with HE, Picrosirius Red and subjected to immunohistochemical analysis of proteins Caspase 3, Caspase 8, Bax, Bid and Bcl-2. Increase in number of vessels was not associated to increase in vascular area, during progression of gestation. The results of histomorphometry revealed increased labeling for Bax and Caspases 3 and 8 in trophoblastic binucleated cells in late pregnancy, awhile Bid remained without significant change. Histomorphometry analyzing the mononuclear trophoblast cells showed a high expression for Bax in early pregnancy, but decreased at 6 months of gestation. Immunolabeling revealed increased Caspases 3/8 and Bid with advancing of gestation. Further evaluation of type I and III collagens showed a decrease of both types of collagens at the end of gestation, which is very important to decrease maternal-fetal adhesion. The dissociation of the fibers of the stroma of chorionic villi decreased at 9 months of gestation, unlike the apoptotic index, which increased progressively with advancing gestation. These results confirm that Caspases 3 and 8 and Bax are involved in the mechanisms of activation of apoptosis through mitochondrial intrinsic and or extrinsic pathway during pregnancy in trophoblastic binucleated cells. In mononuclear trophoblast cells Bax loses importance in the apoptosis process, awhile Bid and caspases 3 and 8 become the most significant.